PEMBERDAYAAN MASYARAKAT PESISIR MELALUI EKOWISATA MANGROVE DI DESA LONTAR KABUPATEN SERANG - Paryadi, Riyo; Ulpah, Maria; Maryatini, Maryatini; Farida, Ida; Hanafiyah, Millatun; Damhudi, Dedi; Kusnady, TB.Heri; Basrowi, Basrowi; Nuryanto, Uli Wiladan (Batara Wisnu : Indonesian Journal of Community Services, 2023)
The potential for mangrove ecotourism in Lontar Village, Tirtayasa District, Serang Regency has great potential as an effort to improve the economy of the region. community understanding regarding the development of mangrove ecotourism potential and providing forms of conservation-based training as a form of community understanding of ecotourism potential in Lontar Village, Tirtayasa District, Serang Regency. the method used is counseling and training for community groups which later these groups will provide education to other communities about managing ecotourism tourism and preserving the environment Data collection techniques through pre-test and post-test, research results show that there is a significant change in the benefits training on increasing public knowledge about mangrove ecotourism